Deviation from symmetrically self‐similar branching in trees predicts altered hydraulics, mechanics, light interception and metabolic scaling. Issue 1 (17th September 2013) - Smith, Duncan D.; Sperry, John S.; Enquist, Brian J.; Savage, Van M.; McCulloh, Katherine A.; Bentley, Lisa P.
Summary: The West, Brown, Enquist (WBE) model derives symmetrically self‐similar branching to predict metabolic scaling from hydraulic conductance, K, (a metabolism proxy) and tree mass (or volume, V ). The original prediction was K ∝ V 0.75 . We ask whether trees differ from WBE symmetry and if it matters for plant function and scaling. We measure tree branching and model how architecture influences K, V, mechanical stability, light interception and metabolic scaling. We quantified branching architecture by measuring the path fraction, P f : mean/maximum trunk‐to‐twig pathlength. WBE symmetry produces the maximum, P f  = 1.0. We explored tree morphospace using a probability‐based numerical model constrained only by biomechanical principles. Real tree P f ranged from 0.930 (nearly symmetric) to 0.357 (very asymmetric). At each modeled tree size, a reduction in P f led to: increased K ; decreased V ; increased mechanical stability; and decreased light absorption. When P f was ontogenetically constant, strong asymmetry only slightly steepened metabolic scaling. The P f ontogeny of real trees, however, was 'U' shaped, resulting in size‐dependent metabolic scaling that exceeded 0.75 in small trees before falling below 0.65. Architectural diversity appears to matter considerably for whole‐tree hydraulics, mechanics, photosynthesis and potentially metabolic scaling. Optimal architectures likely exist that maximize carbon gain per structural investment.